Albumin fusion renders thioredoxin an effective anti-oxidative and anti-inflammatory agent for preventing cisplatin-induced nephrotoxicity - Kodama, A.; Watanabe, H.; Tanaka, R.; Kondo, M.; Chuang, Victor; Wu, Q.; Endo, M.; Ishima, Y.; Fukagawa, M.; Otagiri, M.; Maruyama, T. (Elsevier BV, 2014)
Background: A strategy for preventing cisplatin nephrotoxicity due to enhanced oxidative stress and inflammatory response is highly desirable. Thioredoxin-1 (Trx), an endogenous redox-active protein, has a short retention time in the blood. A long acting form of Trx, human serum albumin-Trx (HSA-Trx), was produced by recombinant HSA fusion and its effectiveness in preventing cisplatin nephrotoxicity was examined. Methods: HSA-Trx was prepared in Pichia expression system. Cisplatin-induced nephropathy mouse model was established by a single administration of cisplatin. Results: Compared to saline, Trx or N-acetylcysteine, an intravenous administration of HSA-Trx attenuated the cisplatin-induced elevation in serum creatinine, blood urea nitrogen and urinary N-acetyl-ß-d-glucosaminidase along with the decrease in creatinine clearance. HSA-Trx caused a substantial reduction in the histological features of renal tubular injuries and the apoptosis-positive tubular cells. Changes in superoxide, 8-OHdG, glutathione and nitrotyrosine levels indicated that HSA-Trx significantly suppressed renal oxidative stress. HSA-Trx also suppressed the elevation of TNF-a, IL-1ß and IL-6. Administered fluorescein isothiocyanate-labeled HSA-Trx was found partially localized in the proximal tubular cells whereas majority remained in the blood circulation. Specific cellular uptake and the scavenging of intracellular reactive oxygen species by HSA-Trx were observed in HK-2 cells. Conclusion: HSA-Trx could be a novel and effective approach for preventing cisplatin nephrotoxicity due to its prolonged anti-oxidative and anti-inflammatory action not only in extracellular compartment but also inside the proximal tubular cell. General significance: We report the renoprotective effect of HSA-Trx against cisplatin nephrotoxicity. This work would enhance developing therapeutics against acute kidney injuries including cisplatin nephrotoxicity.